Quality Assurance System in diagnostic radiology department - Kowski, Ryszard (Contemporary Oncology/Współczesna Onkologia, 2000)
The paper short presents Quality Assurance System, which have to introduce to practice in all radiology departments in Poland. It shows vary accessible step by step the way to implementation this system from the beginning. All those activities have the source in basic principle: ALARA.